Effects of a psychoeducational intervention for direct care workers caring for people with dementia: results from a 6-month follow-up study - Barbosa, Ana (2019)
This study aimed to assess the effects of a psychoeducational intervention, designed to improve direct care workers' stress, burnout and job satisfaction, and person-centered communicative behavior in people with dementia. A pretest-posttest control group design was conducted in 4 aged-care facilities. Two experimental facilities received a psychoeducational intervention, and 2 control facilities received an education only. Data were gathered from 53 care workers at baseline, immediately, and 6 months after the intervention, through self-administrated instruments and video-recorded morning care sessions. The experimental group showed a significant decrease in care workers' burnout and a significant improvement in several communicative behaviors (e.g., involvement). Stress levels deteriorated at 6 months, and no intervention effects were found for job satisfaction. The findings highlight the importance of providing care workers with both technical competences and tools for stress management, as this might be associated with a reduction in their levels of exhaustion and improved communicative behaviors.